Voices of the heart - Young, Ed (New York, NY Scholastic Press, 1997)
From School Library Journal: : Grade 3 Up. In perhaps his most conceptually brilliant work to date, Young introduces 26 Chinese characters, each having the symbol for the heart as a component. An illustration on each page occupies the two-thirds closest to the margin. The outer third has an English word relating to an emotion, feeling, or moral quality (joy, shame, patience, panic, etc.) with a simple definition containing the word heart. Each section (or radical) of the word in Chinese is listed below it with a simple definition of each part and an explanation of the whole, followed by the assembled character for the concept. The Chinese writing is in seal script, which is one of the oldest forms of the language and consequently much closer visually and conceptually to its pictographic origins than today's standard printed forms. This choice is a master stroke as it prepares the mind for the stunning collage illustrations that utilize rebus format to represent the Chinese. Illustrations are of cut paper and some cloth on various paper backgrounds; sometimes backgrounds are textured, sometimes the rebus components are. All contain a heart and are bright or somber depending on the concept conveyed. Though certainly an interesting introduction to Chinese characters, this highly original tour de force will awaken children to the relation between language and thought, providing many hours of fascination and discussion--John Philbrook, formerly at San Francisco Public Library: Copyright 1997 Reed Business Information, Inc.; From Booklist: : Gr. 4-̂8. The splendid scarlet-and-gold jacket will entice readers into this sumptuous picture book, but once in, they might well find themselves confused. At the beginning, Young lists 26 emotions with their modern Chinese characters. He then devotes a page to each emotion, breaking each character into its parts and creating a collage out of the parts and the figure of a heart to express the feeling of the emotion. For example, Contentment is defined as a peaceful heart. The parts of the character are symbols for a claw, work, and a hand; put together they mean After a day of hard work, the heart feels peace of mind. It is content. The accompanying illustration is richly brown like soil, and the heart shape is flecked with shades of brown. Other emotions include panic, rudeness, mercy, and loyalty. For those doing a unit on alphabets or writing, this esoteric book may prove interesting; however, it will require a sophisticated audience willing to examine it closely enough to discern its meaning--Susan Dove Lempke.
Keywords: Emotions -- Juvenile literature; Virtues -- Juvenile literature